The role of CLDN11 in promotion of granulosa cell proliferation in polycystic ovary syndrome via activation of the PI3K-AKT signalling pathway - Min Wang; Tong Chen; Jiani Zheng; Caomeihui Shen; Guitian He; Jingshun Zhang; Boqi Zhang; Lianwen Zheng (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is a complex gynecological endocrinological condition that significantly impacts women’s fertility during their reproductive lifespan. The causes of PCOS are multifaceted, and its pathogenesis is not yet clear. This study established a rat model of PCOS and, in conjunction with clinical samples and database data, analysed the role of claudin 11 (CLDN11) in follicular granulosa cells (GCs) in regulating the proliferation of GCs. Our findings revealed a notable decrease in the protein expression of CLDN11 within the follicular GCs of individuals with PCOS. In vitro rat cell experiments revealed that interference with CLDN11 significantly inhibited viability and increased the apoptosis of GCs. Additional research has illuminated the mechanism by which CLDN11 regulates the expression levels of CCND1 and PCNA through the PI3K/AKT signalling pathway, significantly influencing the proliferation of rat follicular GCs. Furthermore, overexpression of CLDN11 via an adeno-associated virus (AAV) vector was found to reverse the PCOS-like phenotype induced in rats by letrozole. Our findings suggest that CLDN11 stimulates the proliferation of these cells by activating the PI3K/AKT pathway, thereby increasing the expression of CCND1 and PCNA. These discoveries underscore the critical function of CLDN11 in regulating the functionality of follicular GCs, which offers novel insights into the fundamental mechanisms governing PCOS.